2021
DOI: 10.1016/j.sdentj.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of maxillofacial fractures in motor vehicle accidents treated in Dubai

Abstract: Aims To analyze the incidence of maxillofacial fractures due to motor vehicle accidents in Dubai, as well as age, sex, etiology, patterns, treatment, and complications. To compare the findings with similar studies and provide recommendations for the prevention and management of these fractures. Materials and methods A 7-year retrospective study of maxillofacial fractures due to motor vehicle accidents was done. Results We found that most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…who found maximum incidence of fractures in RTAs in Dubai in pedestrians and the mandible was the most involved bone. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…who found maximum incidence of fractures in RTAs in Dubai in pedestrians and the mandible was the most involved bone. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Among the most frequent facial injuries, they identified nasal fractures (43.6%), zygomatic fractures (21.3%), and orbital fractures (20.6%), while mandibular fractures constituted only 3.8% of all maxillofacial injuries. Similarly, several other studies conducted in different regions including Kenya, 17 Philippines, 21 Germany, 20 and the United Arab Emirates 15 have reported that the most frequent anatomical location of accident‐related facial fractures was the midface including fractures of the zygomatic, orbital, and nasal bones. However, some authors have argued that the lower face is more susceptible to fractures in cases of maxillofacial trauma.…”
Section: Discussionmentioning
confidence: 56%
“…Additionally, such data aids in the development of innovative strategies to reduce the incidence of maxillofacial trauma and provide appropriate care by assessing the at‐risk population and identifying contributing factors to trauma 7,11 . The epidemiology of maxillofacial fractures resulting from road traffic accidents has been the subject of several studies conducted in various regions worldwide 9,11–21 . However, no research on maxillofacial fractures specifically caused by rollover crashes has been published to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They occur in about 40% to 60% of victims encountered with trauma. [ 2 ] The type of fractures encountered mostly hinge on the impact of the external forces over the maxillofacial region. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%